Mobilising female labour market reserves: What promotes women's transitions from part-time to full-time work? - Ragni Hege Kitterød; Marit Rønsen; Ane Seierstad (Statistics Norway, Research Department, 2011)
Considering the high female part-time rates in Norway, one may envisage a sizeable additional labour supply if more part-time working women would switch to full time. In view of an ageing population and increased demand for labour in the future, we investigate this issue by studying married and cohabiting women's transitions from part-time to full-time work based on panel data from 2003-2009. Contrary to evidence from other countries with well-established support for working mothers, we find that young children in the household still restrain Norwegian women's mobility to full-time work. On the other hand, there is a strong trend of higher full-time transition rates over our study period, which may reflect a vast expansion of the day care sector with more and cheaper day care, as well as a booming economy. Part timers who work in typical female occupations such as nursing, and sales and services are also less likely to switch to full time. Whether this is a result of true preferences or constraints is difficult to say, but previous research suggest that involuntary part time may be substantial. Voluntariness may further be a matter of degree, and "chosen" part timers may also switch to full time if conditions were right.
Keywords: J21; J22; J24; J13; J16; 330; Female labour supply; part-time; full-time transitions